ANALISIS POTENSI DAUN TORBANGUN (Plectranthus amboinicus) SEBAGAI ANTIBAKTERI TERHADAP Klebsiella pneumoniae SECARA IN SILICO - Nabila Nur Nafiati; Rini Madyastuti Purwono; Nurhidayat Nurhidayat; Laksmi Ambarsari (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Antibiotic-resistant is a global issue. Klebsiella pneumoniae has high priority to find its antibiotic because it has extended-spectrum beta-lactamase (ESBL) enzyme that makes the bacteria easy to resist the antibiotic. The study of phytochemicals in medicinal plants is one of the efforts to find antibiotics. Indrulizia is one of the empirical medicinal plants containing flavonoids used to treat disease. The aim of this study was to analyze the potential of borage as an antibacterial agent against Klebsiella pneumoniae in silico. Docking is the method for this study using AutoDock Vina. This is an application for docking the enzyme ESBL from K. pneumoniae, referred to as SHV (sulfhydryl variable), and the metabolite second from plants. The parameters analyzed were binding free energies, inhibition constants and visualization in 3D and 2D. The free energy of binding and the inhibition constant of the native ligand are -6.7 kcal/mol and 12.118 μM. The binding free energy values ​​of apigenin 7-glucuronide and rosmarinic acid show higher potencies than the native ligand of SHV-1 (1,4-thiazepine).